Seasonal Variation Characteristics of the Symbiodiniaceae Community Associated with Acropora pruinosa from Weizhou Island - Yongqian XU; Biao CHEN; Liangyun QIN; Jinni CHEN; Tianyi NIU; Jiayuan LIANG (Guangdong nongye kexue, 2023)
【Objective】The global coral reef ecosystem is rapidly degrading due to the combined effects of climate change and human activities, which highlights the need to explore the environmental adaptation mechanisms of corals. The environmental adaptability of coral hosts is closely related to symbiotic Symbiodiniaceae, however, the ecological effects of Symbiodiniaceae driven by seasonal variation still need to be further understood.【Method】An environment-sensitive coral Acropora pruinosa from the Weizhou Island, Beibu Gulf was taken as the research object to carry out fixed-point sampling and environmental data monitoring, and analyze the density, community composition, chlorophyll a concentration and correlation with environmental variables of symbiotic Symbiodiniaceae in four different quarters.【Result】The coral reef area was characterized by high temperature and strong light in summer and low temperature and weak light in winter. The density of Symbiodiniaceae and the concentration of chlorophyll a showed the characteristics of decreasing in summer and increasing in winter. The subclade C1 always occupied the dominant position (79.35%-82.97%), and the relative abundance of background subclades such as C1ca, C1p, C72, and Cspc significantly varied with seasonal variation. There were significant differences in the structure of Symbiodiniaceae communities between summer and winter. The contribution of surface seawater temperature (SST) and photosynthetically active radiation (PAR) to the changes in Symbiodiniaceae community structure was higher than chlorophyll a, Kd490, and particulate organic carbon.【Conclusion】The environmental characteristics of high temperature and strong light in summer and low temperature and weak light in winter on Weizhou Island regulate the seasonal changes of Symbiodiniaceae density and chlorophyll a concentration by affecting the photosynthesis of Symbiodiniaceae. Moreover, the physiological characteristics of the C1 subclade ensure that A. pruinosa can adapt to the environment of Weizhou Island. In addition, the SST and PAR affect the abundance changes of the background Symbiodiniaceae, leading to significant differences in community structure.The correlation analysis showed that the SST and PAR were the main factors driving the changes of density, stable symbiosis (subclade C1), and community structure of Symbiodiniaceae. This study took A. pruinosa as an example to analyze the micro-ecological characteristics of coral-associated Symbiodiniaceae adapting to seasonal variation, providing a new understanding about the adaptation of environment-sensitive corals to environmental changes.